Quantum rotor in solid gases: matrix effects on EPR - Dmitriev, Yu. A.; Melnikov, V. D.; Styrov, K. G.; Tumanova, M. A. (Recent Contributions to Physics, 2015)
Our study(a) deals with the methyl radical – the simplest organic radical, which is often observed as a transient intermediate species in chemical reactions. Consequently, it has been widely studied both theoretically and experimentally through decades.